The profile of selected samples of Croatian athletes based on the items of sport jealousy scale (SJS) - Sindik Joško; Bauer Čuk Ana-Mary (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
The role of jealousy in sport, as a negative emotional reaction, accompanied by thoughts of inadequacy when compared to others, is the issue of this article. This study had a purpose to define the characteristic profiles of the Croatian athletes, based on single items of Sport Jealousy Scale (SJS II), labeled by several variables: gender, type of sport, age group. Purposive sample of 73 athletes competing at Croatian championships in different sports (football, bowling, volleyball and handball) were examined with Croatian version of SJS-II. Three clusters obtained are similarly balanced, according to the number of cases in each cluster. The most simply explained, clusters clearly differentiate the most jealous, moderately jealous and slightly/low jealous athletes. Among the features of the athletes in each cluster, in the most jealous (first) cluster are the athletes from team sports, women and older athletes. Females, bowling athletes, athletes from individual (coactive) sports and the youngest athletes are the least jealous (grouped in third cluster).